Efektivitas Pelayanan Program Lanjut Usia Di Pos Pelayanan Terpadu (Posyandu) - Erwin Nugraha Purnama; Ransta L. . Lekatompessy; Dapot Pardamean Saragih; Tri Wijayanti (Universitas Musamus, Merauke, Papua, 2024)
Older adults require a service known as Elderly Integrated Service Posts (Posyandu Lansia) to achieve better health status, independence, and to become healthy, active, and productive, as they often face various health issues, including degenerative and cognitive problems at this stage of life. The purpose of this study is to describe the effectiveness of the Elderly Program Services at the Integrated Service Post (Posyandu) Sumber Mulya. The author used a qualitative descriptive approach. The research method employed was qualitative descriptive techniques, with data collection through interviews, observation, and documentation. To gather research data, the researcher interviewed 13 informants as a sample. Data analysis techniques consisted of three stages: data reduction, data display, and conclusion or verification. The findings revealed that the services for the elderly at Posyandu Kurik 6 Sumber Mulya, Merauke District have not been effective when evaluated using three indicators according to Budiani. Regarding the program’s socialization, it has not been conducted regularly and clearly by the organizers. Additionally, the goal achievement has also been ineffective, both in terms of the implementation process and in phases, and monitoring indicators have not been properly conducted by the organizers. Furthermore, there is a lack of concern from volunteers and midwives for the elderly community members who are unable to attend the Posyandu Lansia program.